Attack efficiency in first league men`s volleyball for playing positions, according to the value level of the teams - Mocanu, G. D.; Harabagiu, N.; Parvu, C. (Pedagogy of Physical Culture and Sports, 2024)
Background and Study Purpose. The attack is a crucial technical element in scoring points in volleyball. This research aims to identify differences in attack efficiency and errors based on the value level of teams in the competitive system, considering different playing positions.